2014
DOI: 10.1371/journal.pone.0099021
|View full text |Cite|
|
Sign up to set email alerts
|

Prescribing Pattern of Anti-Parkinson Drugs in Japan: A Trend Analysis from 2005 to 2010

Abstract: ObjectiveTherapeutic options for Parkinson's disease mainly consist of L-dopa and dopamine agonists. However, in Japan, the product labeling of the ergot dopamine agonists, cabergoline and pergolide, was revised in April 2007 due to the risk of developing cardiac valvulopathy. Here, we describe the prescribing trends of anti-Parkinson drugs from 2005 through 2010 in Japan, and examined whether these trends changed after the drug safety measures in 2007.Methods and PatientsWe used medical claim data from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 37 publications
9
57
1
4
Order By: Relevance
“…We observed that the non-ergot DA class was the second most prescribed anti-PD drug in patients with newly diagnosed PD and was prescribed mainly in younger patients, as recommended in the 2011 Japanese guidelines. This rate was much lower than that reported in a study using the Japan Medical Data Center database between 2007 and 2010 (29.4%) [13]. The Japan Medical Data Center database contained a much greater proportion of younger patients than the MDV database as it consisted of employment insurance [15].…”
Section: Plos Onecontrasting
confidence: 58%
See 1 more Smart Citation
“…We observed that the non-ergot DA class was the second most prescribed anti-PD drug in patients with newly diagnosed PD and was prescribed mainly in younger patients, as recommended in the 2011 Japanese guidelines. This rate was much lower than that reported in a study using the Japan Medical Data Center database between 2007 and 2010 (29.4%) [13]. The Japan Medical Data Center database contained a much greater proportion of younger patients than the MDV database as it consisted of employment insurance [15].…”
Section: Plos Onecontrasting
confidence: 58%
“…Previous database studies from the United States [8][9][10][11], Taiwan [12], and Japan [13] have examined prescribing patterns for PD. However, the Japanese study reported data obtained before publication of the 2011 guidelines, and new anti-PD drugs have been approved and new data regarding the risk of side effects have been reported since then [14].…”
Section: Introductionmentioning
confidence: 99%
“…No study has reported the association between the use of zonisamide and the incidence of PD-relevant symptoms in comparison with other anti-PD drugs. Nakaoka et al analyzed claims data that was collected from January 2005 to November 2010 and reported about zonisamide use [35]. However, they mainly reported the prescribing trends of zonisamide as well as other anti-PD drugs.…”
Section: Comparison With Previous Similar Studiesmentioning
confidence: 99%
“…Since 1991, evidence-based medicine (EBM) has been adopted in various clinical fields along with an increase in social awareness that seeks high-quality medical care (1). However, it is not always the case that evidencebased medical care is practiced in clinical settings (2)(3)(4)(5)(6)(7). One study reported that guideline-recommended medical care is provided to roughly 50% of adult patients (8).…”
Section: Introductionmentioning
confidence: 99%